The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/marc.200900843
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hofmeister Salts on the LCST Transition of Poly(2‐oxazoline)s with Varying Hydrophilicity

Abstract: The influence of Hofmeister salts was investigated on the cloud point of three poly(2-oxazoline)s, namely poly(2-ethyl-2-oxazoline) [PEtOx], poly(2-n-propyl-2-oxazoline) [PnPropOx], and poly(2-isopropyl-2-oxazoline) [PiPropOx]. In addition, a comb polymer based on oligo-2-ethyl-2-oxazoline side chains and a methacrylate backbone (POEtOxMA) was included in this investigation. It was found that the ionic response of the poly(2-oxazoline)s strongly depends on their hydrophilicity. The comb polymer POEtOxMA reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 30 publications
9
146
0
Order By: Relevance
“…Those findings are in good agreement with previous observations for the LCST behavior of comb shaped pEtOx when compared to its linear analogue. 24,35 The formation of aggregates of pCPropOx with varying DP was investigated in further detail by dynamic light scattering (DLS) measurements at a concentration of 1 mg mL À1 at different temperatures. At a certain temperature the hydrodynamic radius (R h ) measured by DLS increases from the characteristic size of individual polymer chains (<10 nm) to the size of larger aggregates (>100 nm) (Figure 6a and ESI).…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Those findings are in good agreement with previous observations for the LCST behavior of comb shaped pEtOx when compared to its linear analogue. 24,35 The formation of aggregates of pCPropOx with varying DP was investigated in further detail by dynamic light scattering (DLS) measurements at a concentration of 1 mg mL À1 at different temperatures. At a certain temperature the hydrodynamic radius (R h ) measured by DLS increases from the characteristic size of individual polymer chains (<10 nm) to the size of larger aggregates (>100 nm) (Figure 6a and ESI).…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…In a later study, these investigations were expanded to p i PrOx-stat-p n BuOx, which molecularly dissolved below the cloud point temperature in water and were incorporated into micellar nanoparticles of Pluronic F127 after increasing the solution temperature beyond their transition temperature [146]. Furthermore, copolymerizations with [147]. It was shown that the response to the addition of Hofmeister salts depended significantly on the (degree of) hydrophilicity of the polymers, but hardly on their architecture.…”
Section: S-galactosyl Substituents Namely (5oac·gal-s)etox and (5oacmentioning
confidence: 99%
“…Furthermore, PEtOx can be salted out from aqueous solution by the addition of sodium chloride, leading to a decrease of the LCST, whereas the opposite effect is observed with tetrabutylammonium bromide [16]. A more extensive study on salting in and salting out effects of a range of Hofmeister ions on different thermoresponsive poly(2-alkyl-2-oxazoline)s was recently performed by Hoogenboom and Schubert [18]. In 1992 Kobayashi et al introduced poly(2-isopropyl-2-oxazoline) (PiPrOx) as a thermoresponsive polymer exhibiting a cloud point in the range from 36 to 39 °C [19].…”
Section: Thermoresponsive Poly(2-oxazoline)s In Aqueous Solutionmentioning
confidence: 99%